RANCANGAN BRAIN BASED LEARNING DALAM MENINGKATKAN MOTIVASI BELAJAR PENDIDIKAN AGAMA ISLAM SEKOLAH DASAR - Baroroh, Umi; Prastowo, Andi (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2023)
One of the important factors that influence student activity in learning is motivation. Ideally, every student has a strong motivation in following each subject, including Islamic Religious Education (PAI). However, the reality is that there are still many students who are demotivated in learning PAI. This happens because in the PAI learning process it is only a transfer of material and is rote. Thus, teachers need to strive for learning that is in harmony with how the brain works so that students are motivated to learn PAI. This study aims to describe the design of brain-based learning (Brain Based Learning). This research is in the form of library research using a descriptive analytical approach to the Brain Based Learning themes of Eric Jensen's thinking. In this study it was found that to increase students' learning motivation with a Brain Based Learning model, the following steps could be taken: pre-exposure, preparation, initiation/acquisition, elaboration, memory formation, reinforcement, celebration and integration